PREVENTING MEASURE TOWARDS THE EFFECT OF N95 MASKS PERFORMED BY HEALTH WORKERS DURING THE COVID-19 PANDEMIC - M. Rusli; Kadek Ayu Erika; Yuliana Syam (International Conference on Social and Islamic Studies, 2021)
This study aims to identify the actions of health workers in preventing the effects of N95 masks. In preparing this review, the study design used was a literature review. Article searches were conducted through electronic databases and websites, namely Pubmed, Proquest, ScienceDirect and Wiley. The results of the analysis of 9 research articles showed that, there were articles that reported the use of dressings was effective to prevent injury and provide a sense of comfort, also there were no injuries but caused discomfort, and there were those who reported more pressure injuries with the use of prophylactic dressings than those that did not use. In conclusion, preventive measures with prophylactic dressing on the use of N95 masks still require further research.